19 Comparing stress indicators of horses used for therapy in riding activities and groundwork activities. (28th November 2020) - Abbott, Gabrielle; Jogan, Kathi; Oberhaus, Erin L; Apple, Jason; Rosenkrans, Charles
Abstract: Equine therapy is used to assist people suffering from various physical and mental disabilities. Equine-assisted activities and therapies (EAAT) include therapeutic riding and hippotherapy. Our objective was to determine the effects of EAAT on horse heart rate, respiration rate, temperature, and serum cortisol. Horses (n = 7) were assigned to activity type (groundwork or riding) in a Latin square design in which all horses performed both activities twice. Heart rate, respiration rate, rectal temperature, and serum cortisol concentrations were determined at 15 minutes before, and 15, 45, and 75 minutes after activity was initiated. Pearson correlations revealed that cortisol was not correlated (r < 0.12; P > 0.22) with heart rate, respiration rate, or rectal temperature. Heart rate was correlated (P < 0.05) with respiration rate (r = 0.77) and body temperature (r = 0.2); and body temperature was correlated with respiration rate (r = 0.21; P < 0.05). Analysis of variance was performed with horse within date as the experimental unit, main effects of activity type, horse, date, experimental time, and interactions. Serum concentrations of cortisol (varied from 2.8 to 89.7 ng/mL) and body temperature (37.4 ± 0.06) were affected (P < 0.01) by an interaction between experimental time and horse. Heart rate (61 ± 2.1) and respiration rate (30 ± 1.4) were affected (P < 0.01) by interactions between experimental time and horse; and experimental time and activity type. Our results demonstrate that equine athletes serving in EAAT programs have altered physiological responses depending on the horse, type of activity, and length of time performing the task. Based on our results, cortisol concentrations are not the best indicator of a horse's response to EAAT work, and we recommend that trainers monitor horses' heart and respiration rates as an indicator of horse well-being while working with patients.